Effect of spacing and variety on potato seed tuber production in eastern Uganda (Makerere University Journal of Agricultural & Environmental Sciences, 2004)
In the highlands of eastern Uganda, potato (Solanum tuberosum) productivity per unit area is constrained by limited availability of quality seed. This study evaluated the effect of plant spacing and variety on potato seed tuber production at three locations in eastern Uganda. Two varieties and four different spacings were used. Results for all locations and seasons showed that close plant spacing (20 x 20 cm) produced significantly (P = 0.05) highest potato seed tubers, total tubers and tuber yield per unit area while seed tubers were least at widest crop spacing of 70 x 30 cm. However, high plant density resulted in significantly (P = 0.05) reduced average tuber weight. Variety x spacing interactions were not significant for most variables, indicating that reducing spacing was the most critical factor for determining tuber size number.
Keywords: Quality seed; seed-size tubers; Solanum tuberosum